Kajian Aksiologi Terhadap Fungsi Profesionalitas Guru Dalam Pembentukan Karakter Siswa Pada Pembelajaran Daring [An Axiology Review on the Function of Teachers' Professionality in Building the Students' Character During Online Learning] - Mikael Faradaey; Tanti Listiani (Universitas Pelita Harapan, 2022)
Online learning is a learning method which conducted during the Covid-19 pandemic and focuses on students as active learners. As human, students are image of God yet fallen into sin, which makes them create the understanding of good and bad. Therefore, teachers need teacher’s professionalism to guide students, who have problems character during online learning, to stay on the right path and grow. The purpose of this paper is to see the role of teacher professionalism in shaping the character of students to interpret Christian education in online learning. The method used in this paper is a literature review. Teachers can carry out character building with the Pancasila profile framework and focus on the character of Christ. This can be achieved by delivering learning materials referring to the profile of Pancasila students and the character of Christ in the lesson plans by preparing biblical Christian worldview which carried out professionally. The professional attitude of teachers in carrying out their duties and responsibilities in the classroom helps the learning process run well by fulfilling the focus in cognitive, affective, and psychomotor.